Les effets socio-économiques et paysagers du système coopératif viticole en territoires de montagne - Etienne Delay; Marius Chevallier; Eric Rouvellac; Fabio Zottele (Revue de Géographie Alpine)
In an economy of increased globalization and trade, wine holds a privileged place. The wine cooperative system in vineyards in mountain regions, such as in Banyuls-sur-Mer, France and the Val di Cembra, Italy, offers a privileged context for studying the opportunities for individual action that affect precarious socio-economic balances. To understand, and sometimes predict, changes in the socio-economics and landscapes of a region due to cooperatives, we have used a multi-agent system (MAS) to model the behavior of the actors involved in wine production in a cooperative. This model analyses cooperative systems’ impact on socio-economic factors (income inequality and the rate of business failure) and landscapes (percentage of total land as vineyards, particularly in steep areas) of the regions considered. The findings show that cooperatives play a role of socio-economic and landscape stabilizer in these regions.